Моделирование износа алмазного бурового долота - Бондаренко, Н.А.; Жуковский, А.Н.; Мечник, В.А.; Супрун, М.В.; Коростышевский, Д.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The approach for studying the kinetics of diamond drill bit wear in hole drilling conditionsis developed. The model takes account of the differential equation for abrasive wear, the coefficientdependence upon temperature, radial and tangential thermoelastic stresses and sliding velocity.The final expressions are obtained in an explicit form, they enable to define the components ofquasi-static thermoelastic stresses at a random point of time and to analyze the main factors influ-encing on kinetics of the given process.